Artistic Strategies for Scenography Training. A Study Case: The course on Scenography at the Universidad de Málaga. - Lopez-Rodriguez, Silvia; Alonso-Calero, José María (Academic Star, 2019)
This paper deals with some training approaches on the course on Scenography taught at the Universidad de Málaga’s Fine Arts School, Spain. The course, included in the Sculpture course of study, aims at exploring the artistic creation process involved in scenography design and caters for some active participation of students to enhance their creativity and research-based artistic and experimental thinking, both formally and conceptually, as defined in Julio Cortázar’s short story book Cronopios and famas. The main course objective is to set up a training time and space where students can research, create and develop new expressive and symbolic alternatives to further design and provide their own scenography proposals. The paper further reviews some theories published on creativity in the artistic arena and on the creation process itself by using Cortázar’s literature as a starting point.
JMER es una revista internacional, de investigación en educación, revisada por pares, publicada mensualmente en inglés por Academic Star Publishing Company, EE. UU. Indexada en: Crossref , ICI Journals Master List / ICI World of Journals, Worldcat, PBN/POL-Index, Ulrich's periodicals, Google Scholar, SSRN, Index Copernicus International. http://www.academicstar.us/journalsshow.asp?ArtID=365&showa=show_sub
Keywords: Escenografía - Estudio y enseñanza; Scenography; artistic creation process; sculpture course; experimental thinking; creative process; Julio Cortazar